PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN VARIABEL MEDIASI SUPERVISOR TRUST - Sindhu Putra Tanujaya (Universitas Katolik Soegijapranata Semarang, 2015)
Organizational Citizenship Behavior (OCB) is one of the indicators in improving the effectiveness of an organization's performance. Factors that may affect the formation of OCB in organizations include transformational leadership and trust supervisor. Transformational leadership style is a style that is performed by superiors to subordinates by providing motivation and an example to a task or job that is given by superiors to subordinates in the organization. Supervisor trust is a trust level that is owned by subordinates to superiors. OCB is a voluntary behavior that appears within the individual in order to achieve organizational goals. This study used 70 respondents from the banking sector employees in Semarang as samples and data are processed as many as 49 samples. Testing tools in this research by using SPSS and with multiple regression analysis with significance level of 5%. The results of this study indicate that transformational leadership style influence on the formation of Organizational Citizenship Behavior (OCB) when through the supervisor trusts.